In Vitro Comparison of Apically Extruded Debris during Root Canal Preparation of Mandibular Premolars with Manual and Rotary Instruments - Soi, Sonal (J Dent Res Dent Clin Dent Prospects, 2015)
Background and aims. During root canal preparation, debris extruded beyond the apical foramen may result in periapical inflammation and postoperative pain. To date no root canal preparation method has been developed that extrudes no periapical debris. The purpose of this study was to identify a system leading to minimal extrusion of debris from the apical foramen. The study was conducted to comparatively evaluate the amount of apical extrusion of debris during root canal preparation using hand ProTaper and GT rotary and RaCe rotary instruments using crown-down technique. Materials and methods. Ninety freshly extracted human single-rooted mandibular premolars were equally assigned to three groups (n=30). The root canals were instrumented using hand ProTaper, GT rotary and RaCe rotary systems. Debris and irrigant extruded from the apical foramen were collected into vials. The mean weight of the remaining debris was calculated for each group and subjected to statistical analysis. Results. ANOVA was used to compare the mean dry weights of the debris extruded in the three groups, followedby post hoc Tukey tests for multiple comparisons the between groups. Highly significant differences were found in the amount of debris extruded among all the groups (P<0.001). The ProTaper group exhibited the highest mean debris weight (0.8293±0.05433 mg) and the RaCe system exhibited the lowest mean debris weight (0.1280±0.01606 mg). Conclusion. All the systems tested resulted in apical extrusion of debris. However, the hand ProTaper files extruded a significantly higher amount of debris than GT and RaCe systems.